Kirkeforfatningsspørgsmålet 1848-1901 - Andersen, Steen Skovgaard (Kirkehistoriske Samlinger, 1992)
The article presents and discusses the question of church government in Denmark from 1848 to 1901. In Denmark’s first democratic Constitution, the »Basic Law of the Realm of Denmark of June 5th 1849, the religious rights of the citizens were codified, and the state-church of absolutism was replaced by a Folkekirke, a People’s Church. The bonds between state and church were, however, upheld, as the Constitution did not stipulate anything about the organisation of Church affairs. It had been the intention of the men behind the Constitution that the Church as an organism in its own right was at a later stage to have its own representative government with the task of regulating the internal affairs of the Church as well as its relations to the State. This was, however, not how things came to be. Clergy as well as politicians were deeply divided over the question of church government. Bishop Mynster and his followers wanted to keep the statechurch. The High Church people, headed by professor H. L. Martensen, strove to develop historical institutions such as diocesan conferences and their assistant institutions, in order to make a constitution grow from the roots, whereas the theological professor H.N. Clausen and the Liberals wanted a more independent-like church government. In Parliament also, it proved impossible to reach agreement, as politicians with sympathy for the claims of the peasants, as well as Grundtvigian (Broad Church) members, and several National Liberals were opposed to a form of church government which would curtail the influence of Parliament on ecclesiastical legislation. They believed not only that Parliament had a constitutional right to legislate in church matters, but also that Parliament was best suited to represent the national Church. The National Liberals, who occupied seats in the changing governments between 1848 and 1864, therefore chose to solve church problems by ad hoc legislation to regulate external matters, and by Royal decrees as far as internal ones were concerned. After the war of 1864 the National Liberals, who were landed with the responsibility for the defeat, had to cede power to conservative forces who in 1866 reached an agreement with the representatives of the small farmers on a revision of the Constitution. The new Constitution secured a permanent majority for the big land-owners in the Upper House of Parliament, but limited the political influence of the small farmers. These, in reaction to this development, found a new ally in the Venstre party which, in addition to Parliamentary government responsible to the Lower House, also demanded both more freedom for the Church and continued Parliamentary influence on church affairs. Up till 1874 several church acts were passed in Parliament, among which was the Act legalizing congregations formed by the voluntary union of a certain number of members of the Established Church. This measure was forced through by the Government in order to win the support of the Grundtvigians for a number of important reforms of domestic policies. Shortly after the passing of this Act a Church Commission was convened to consider a representative Church Constitution, but the Grundtvigians in Parliament obstructed the Constitution Bill introduced by the majority of this commission. After 1875, the year in which the big land-owners led by J. B. S. Estrup formed a government, church matters were overshadowed by the constitutional struggle. Thus church legislation was very scarce during the years from 1875 to 1901; and the Ministry of Culture consequently was able to play a dominant role in church administration. When in 1883 the Government administratively set up the Church Council, consisting of the bishops, a professor of theology, and a professor of law, many members of the clergy hoped for greater freedom for the Church in its relation to the State and an opportunity to lay the foundation for a Church Constitution. But the Church Council never became truly reprensentative, and the problems of finding a united stand gradually weakened its authority both with the Ministry and with the clergy. The Council therefore soon gave up solving the church government problem and concentrated instead on liturgical reforms. Shortly after Venstre’s coming to power in 1901, J.C. Christensen abolished the Council and set to work on church affairs.